The impact of emotional intelligence on life satisfaction among Chinese nurses: A chain mediating model - Qin, Yuan; Liu, Jiao; Wu, Dongmei (Frontiers in Psychology, 2023)
Introduction Nurses’ life satisfaction exerts a positive impact on their professional careers, and it seriously affects their physical and mental health. Low life satisfaction has become a key factor in the global shortage of nurses. Emotional intelligence may protect nurses from negative emotions that can affect the care they provide, as well as their life satisfaction. In this study, we aims to explore the impact of emotional intelligence on life satisfaction, and even verify the chain mediating effect of self-efficacy and resilience on this relationship among Chineses nurses. Method The Emotional Intelligence Scale, the General Self, Efficacy Scale, the Connor-Davidson Resilience Scale, and the Satisfaction with Life Scale were used to survey 709 nurses in southwest China. To analyze mediating effects, SPSS 26.0 and Process V3.3 were used for statistical processing. Result Emotional intelligence positively predicted life satisfaction. Meanwhile, it was also found that emotional intelligence and life satisfaction were continuously mediated by self-efficacy and resilience, and the indirect effect value was 0.033, accounting for 17.37%. Conclusion This study reveals how emotional intelligence affects nurses’ life satisfaction. The results of this study have certain implications for nurses to better balance their career and life. Nursing managers should provide nurses with a favorable working environment from the perspective of positive psychology, improve their sense of self-efficacy and resilience, ultimately improve their life satisfaction.